STUDENTS’ PROBLEMS OF ACADEMIC WRITING COMPETENCIES, CHALLENGES IN ONLINE THESIS SUPERVISION, AND THE SOLUTIONS: THESIS SUPERVISORS’ PERSPECTIVES - Nurkamto, Joko; Djatmika, Djatmika; Prihandoko, Lastika Ary (TEFLIN Journal, 2022)
The COVID-19 outbreak has brought about the offline-to-online transformation of EFL undergraduate thesis supervision along with its challenging complexities. Anchored in a combination of realistic and constructivist epistemologies, this explanatory sequential design of mixed-method research aimed to investigate students’ problems of academic writing competencies, challenges in online thesis supervision, and solutions to the problems and challenges according to thesis supervisors’ perspectives. Data was first gathered using a closed-ended questionnaire involving fifty thesis supervisors from Central Java and Papua universities as the respondents. Descriptive statistical analyses were conducted to process this data. Twenty-three of the respondents were then purposively selected for interviews and focus group discussions, the data of which was analyzed using interactive model-driven analyses. This study revealed students’ problems of academic writing competencies covering the dimensions of thesis elements and writing performances. Subsequently, multiple challenges were unraveled pertaining to the issues of technological competencies, time management, complexities of students’ field research, and students’ unstable motivation. The supervisors proposed contextual solutions and those demonstrating their interventions for improving students’ metacognition, self-efficacy, and growth mindsets in academic writing. Further studies are expected to work on more in-depth mixed-method investigations that examine the interactions of motivational and strategic constructs predicting academic writing competencies to dive more deeply into the problems, challenges, and solutions concerning the online thesis supervision